10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Dermatophytosis is a global infection with increasing reports of resistance among its causative agents in recent years. As a result of this issue, new therapeutic options are needed. The calcineurin-calmodulin pathway is critical for fungi. Inhibitors of this pathway, such as tacrolimus in combination with antifungal drugs, may serve as alternative treatments. Nanoformulation is another method to address challenges in dermatophytosis treatment. Thirty dermatophyte isolates were included in this study. Antidermatophyte activities of terbinafine, itraconazole, posaconazole, nanoposaconazole, and tacrolimus were investigated using the third edition of the CLSIM38 protocol. In vitro interactions between tacrolimus and the antifungal drugs were studied using a checkerboard method. The isolates included Trichophyton indotineae (n = 14), Trichophyton tonsurans (n = 9), Trichophyton interdigitale (n = 6), and Microsporum canis (n = 1). Tacrolimus demonstrated moderate inhibitory effects against all species. Itraconazole had the strongest activity; however, based on EUCAST epidemiological cutoff values, one T. indotineae isolate was non-wildtype to this drug. Additionally, 10 out of 14 (71.42%) isolates of this species were non-wild type to terbinafine. Nanoposaconazole showed superior antifungal activity compared to posaconazole. Regarding drug combinations, the highest and lowest synergistic rates were observed for combinations of tacrolimus with nanoposaconazole (15/30, 50%) and itraconazole (4/30, 13.33%), respectively. The high rate of non-wildtype T. indotineae isolates to terbinafine underscores the necessity of precise identification to prevent treatment failure. Itraconazole proved to be the most effective antifungal. Combining tacrolimus with antifungal drugs, particularly nanoposaconazole, shows promise and warrants further investigation.